Renewed rationale for sex- and gender-disaggregated research: A COVID-19 commentary review. (February 2022) - Thompson, Kelly; Vassallo, Amy; Finfer, Simon; Woodward, Mark
The COVID-19 pandemic provides a contemporaneous illustration of the need to consider sex and gender in research. Using surveillance, treatment and vaccine research examples, in this commentary review, we highlight opportunities for innovation in sex- and gender-sensitive and transformative health and medical research.